2022
DOI: 10.3389/fmicb.2022.835931
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Insights Into Endophyte-Derived Bioactive Compounds

Abstract: Among the various plant-associated microbiota, endophytes (the microbial communities inhabiting plant endosphere without causing disease symptoms) exhibit the most intimate and specific association with host plants. Endophytic microbes influence various aspects of plant responses (such as increasing availability of nutrients, tolerance against biotic and abiotic stresses, etc.) by modulating the primary and secondary metabolism of the host. Besides, endophytic microbes produce a diverse array of bioactive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 89 publications
(96 reference statements)
0
25
0
Order By: Relevance
“…Metabolomics are often classified into two groups: untargeted metabolomics, a comprehensive analysis of numerous known/unknown metabolites in the sample, and targeted metabolomics, the measurement of the specific metabolites in the sample [ 152 ]. Untargeted metabolomics can be performed to discover novel compounds, and targeted metabolomics is able to validate the results of untargeted metabolomics [ 153 ]. As described by Liu et al, the high-performance liquid chromatography-mass spectrometry (HPLC-MS) based analysis showed that 88 secondary metabolites including 70 novel natural products were produced by Pestalotiopsis fici isolated from healthy Camellia sinensis (Theaceae) [ 154 ].…”
Section: Multi-omics Approaches For Mining Bioactive Metabolites From...mentioning
confidence: 99%
“…Metabolomics are often classified into two groups: untargeted metabolomics, a comprehensive analysis of numerous known/unknown metabolites in the sample, and targeted metabolomics, the measurement of the specific metabolites in the sample [ 152 ]. Untargeted metabolomics can be performed to discover novel compounds, and targeted metabolomics is able to validate the results of untargeted metabolomics [ 153 ]. As described by Liu et al, the high-performance liquid chromatography-mass spectrometry (HPLC-MS) based analysis showed that 88 secondary metabolites including 70 novel natural products were produced by Pestalotiopsis fici isolated from healthy Camellia sinensis (Theaceae) [ 154 ].…”
Section: Multi-omics Approaches For Mining Bioactive Metabolites From...mentioning
confidence: 99%
“…Microorganisms have been observed to enter host plants through roots and colonize plants (Chi et al, 2005;Thomas and Reddy, 2013). It has been reported that among the various plant-associated microbiota, endophytic microorganisms exhibit the most intimate and specific association with host plants (Vasileva et al, 2019;Mishra et al, 2022). There is growing evidence that the endophytic microorganisms support plants against both biotic and abiotic stresses (Ludwig-Muller, 2015;Sugio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial compounds may also be used as food preservatives among other biotechnological applications [ 13 ]. Furthermore, advances in chromatography and spectroscopy techniques have smoothened the path of rapid identification of known and unknown secondary metabolites [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%